The competition-stability nexus of South African Banks - Zhou, Linear R (My University, 2017)
This study is necessitated by the debate about competition in the banking sector of South Africa based on the dominance of the big four banks and is premised on establishing the effect of competition on financial stability. It is propelled by the reactionary recalibration of fiscal and monetary policies to reinstate system stability owing to post-crises system instabilities which manifested over 1990-2015 in addition to the aggregation of competition indices at country and bank level as well as the misnomer that likens concentration to competition. The research complements existing literature by and inferring the effect of competition on stability, over the duration 1990-2015 and debunking the concentration-competition misnomer. It also maps the competitive terrain of the South African banking market by utilising a two- pronged estimation approach. Initially competition is estimated using a log-transformation method to calculate the Lerner, Adjusted Lerner indices and H-statistic. Followed by, calculation of the Z-Score. The study then uses the results from the three indices to exhaustively affirm monopolistic competition as the predominant competitive environment in South Africa. Using the Z-score and Lerner indices with OLS estimation methods incorporating robust standard errors, the study posits the relationship between competition and stability and suggests that South Africa is inclined towards competition-fragility. These finding are aligned with preceding studies of a similar nature and have implications for policy formulation in addition to adding value to banking theories on banking crises and competition. The outcomes have connotations for policy formulation, suggesting that while South African Banks are monopolistically competitive, there is room to harness the spill overs from macro-economic indicators of financial health and stability for instance through improved access to finance and bank alliances that will enhance the prospects of Small and Medium Enterprises. In addition, the South African Government through its agency of regulation and supervision is better placed to maintain financial stability armed with the mechanism for setting reforms in a monopolistic competition environment.
Submitted in accordance with the Master of Management in Finance & Investment Degree for University of Witwatersrand: Business School Under the faculty of Commerce Law and Management